2017
DOI: 10.1099/ijsem.0.002192
|View full text |Cite
|
Sign up to set email alerts
|

Winogradskyella haliclonae sp. nov., isolated from a marine sponge of the genus Haliclona

Abstract: A yellow-pigmented, Gram-stain-negative, motile and rod-shaped bacterium, strain M1A16, was isolated from the internal tissue of a sponge of the genus Haliclona, which was long-term cultured in the CEMarin aquaria system at Justus Liebig University of Giessen. The strain grew well at 20-32 °C (optimum 25 °C), in the presence of 0-6 % NaCl (optimum 3 %), and at pH 5.5-9.0 (optimum pH 7.0-8.0). Phylogenetic analysis based on its 16S rRNA gene sequence placed the strain within the monophyletic cluster of the genu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…OTUs assigned to the Bradyrhizobiaceae family have previously been observed in oysters (Sakowski, 2015), however, due to the coarse taxonomic assignment of this OTU, it is unclear what potential role this member of the Bradyrhizobiaceae family might have. Winogradskyella species are commonly found in numerous marine organisms, including oysters (Valdenegro-Vega et al, 2013; Park et al, 2015; Lee et al, 2017; Schellenberg et al, 2017; Franco et al, 2018), and are known for their role in amoebic-induced fish gill diseases (Embar-Gopinath et al, 2005, 2006). However, it is uncertain what function(s) Winogradskyella species play in oysters.…”
Section: Discussionmentioning
confidence: 99%
“…OTUs assigned to the Bradyrhizobiaceae family have previously been observed in oysters (Sakowski, 2015), however, due to the coarse taxonomic assignment of this OTU, it is unclear what potential role this member of the Bradyrhizobiaceae family might have. Winogradskyella species are commonly found in numerous marine organisms, including oysters (Valdenegro-Vega et al, 2013; Park et al, 2015; Lee et al, 2017; Schellenberg et al, 2017; Franco et al, 2018), and are known for their role in amoebic-induced fish gill diseases (Embar-Gopinath et al, 2005, 2006). However, it is uncertain what function(s) Winogradskyella species play in oysters.…”
Section: Discussionmentioning
confidence: 99%
“…1987), disadvantages might be easily outweighed by benefits of particles providing organic material and shelter from extreme levels of ultraviolet and solar radiation experienced at the air-sea boundary. The LefSe analysis revealed that Winogradskyella ( Flavobacteriaceae ), often being associated with brown algae or sponges (Park and Yoon 2013; Schellenberg, et al . 2017; Yoon and Lee 2012), was abundant among the metabolically active OTUs in foams (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Although attachment to particles might have some drawbacks for bacteria regarding grazing (Albright, et al 1987), disadvantages might be easily outweighed by benefits of particles providing organic material and shelter from extreme levels of ultraviolet and solar radiation experienced at the air-sea boundary. The LefSe analysis revealed that Winogradskyella (Flavobacteriaceae), often being associated with brown algae or sponges (Park and Yoon 2013;Schellenberg, et al 2017; Yoon and Lee 2012), was abundant among the metabolically active OTUs in foams ( Figure 6). As broken algal cells and detritus are major parts of foams, high relative abundance of Winogradskyella in the foam particle-associated fraction ( Supplementary Figure 11) might be due to its attachment to algal-derived substrates.…”
Section: The Role Of Particles For Foam-populating Bacteria and Biogementioning
confidence: 99%
“…S4). The sole respiratory quinone of strain ZXX205 T was MK-6, which is also the major respiratory quinone in the most members of the genus Winogradskyella [2, 7–12]. The DNA G+C content of ZXX205 T was 35.5 %, a value in the range reported for recognized species of the genus Winogradskyella (30.1~39.0 mol%) [1–4, 7–12].…”
Section: Full-textmentioning
confidence: 99%
“…Within the genus Winogradskyella, all members have been isolated from marine environments or marine organisms [7], strictly aero-bic or facultatively anaerobic and catalase-positive. Besides W. psychrotolerans (the respiratory quinones of this species are MK-6 and MK-7) [6], the sole or major respiratory quinone of the species in genus Winogradskyella is MK-6 [2,[7][8][9][10][11][12]. The main cellular fatty acids are branched-chain (iso-C 15 : 0 , iso-C 15 : 1 , anteiso-C 15 : 0 ) and fatty acids with hydroxy groups (iso-C 15 : 0 3-OH, iso-C 16 : 0 3-OH, and iso-C 17 : 0 3-OH) [10,12].…”
mentioning
confidence: 99%